Human Leukocyte Antigens Assosiation with Systemic Lupus Arythematosus In Iraqi Patients - Al-Hammamy, Hyam Raouf; Abd, Kais Hasan; Khalil, Iqbal Ali; Mahdi, Batool Mutar (AL-Kindy College Medical Journal, 2012)
Background: The etiology of Systemic lupus erythematosus seems to be multifactorial including environmental as well as genetic factors. The genetic predisposition was supported by the occurrence of Systemic lupus erythematosus in more than one member of a family as well as in identical twins.Aim of the study: To determine the human leukocyte antigen typing class I (A and B) in patients with Systemic Lupus Erythematousus disease.Methods: Patients group consisted of 44 Iraqi Arab Muslims patients with Systemic lupus erythematosus disease who presented to Baghdad Medical City from January 2010 to January 2012 from Baghdad Province. The second control group consisted from 80 Iraqi Arab Muslims volunteers from hospital employees and their relatives. Human leukocyte antigen typing done for them using serological method by microlymphocytotoxicity test.Results: A total of 44 patients with Systemic lupus erythematosus were studied. Patients' age ranged from 6 to 65 years with a mean of 29.61 ± 12.78. The other control group, their ages ranged from 16 to 55 years with a mean of 31.35 ± 10.02 . Females were more than males in both groups. Human leukocyte antigen typing of Systemic lupus erythematosus patients showed A2( 16, 36.36, 0.20), A3( 14, 31.82, 0.17), B4(10, 22.73, 0.12) , B12 (10, 22.73, 0.12) and B21(10, 22.73, 0.12) were the highest absolute numbers, phenotype frequencies and genotype frequencies respectively. There was a significant difference in between SLE patients and control group in the following alleles (A1, A28, A36, A43,B 6, B12, B14, B15, B16, B35, B42, B53).Conclusions: Genetic factors do have a role in the development and expression of Systemic lupus erythematosus . human leukocyte antigen -A28 , A36, B12 and B21 had an association with Systemic lupus erythematosus Iraqi patients.